Different behaviour of DVL1, DVL2, DVL3 in astrocytoma malignancy grades and their association to TCF1 and LEF1 upregulation. Issue 1 (23rd November 2018) - Kafka, Anja; Bačić, Mateja; Tomas, Davor; Žarković, Kamelija; Bukovac, Anja; Njirić, Niko; Mrak, Goran; Krsnik, Željka; Pećina‐Šlaus, Nives
Abstract: Key regulators of the Wnt signalling, DVL1, DVL2 and DVL3, in astrocytomas of different malignancy grades were investigated. Markers for DVL1, DVL2 and DVL3 were used to detect microsatellite instability (MSI) and gross deletions (LOH), while immunohistochemistry and immunoreactivity score were used to determine the signal strengths of the three DVL proteins and transcription factors of the pathway, TCF1 and LEF1. Our findings demonstrated that MSI at all three DVL loci was constantly found across tumour grades with the highest number in grade II ( P = 0.008). Collectively, LOHs were more frequent in high‐grade tumours than in low grade ones. LOHs of DVL3 gene were significantly associated with grade IV tumours ( P = 0.007). The results on protein expressions indicated that high‐grade tumours expressed less DVL1 protein as compared with low grade ones. A significant negative correlation was established between DVL1 expression and malignancy grades ( P < 0.001). The expression of DVL2 protein was found similar across grades, while DVL3 expression significantly increased with malignancy grades ( P < 0.001). The signal strengths of expressed DVL1 and DVL3 were negatively correlated ( P = 0.002). However, TCF1 and LEF1 were both significantly upregulated and increasing with astrocytoma grades ( P = 0.001). A positive correlation was established between DVL3 and both TCF1 ( P = 0.020) and LEF1 ( P = 0.006) suggesting their joint involvement in malignant progression. Our findings suggest that DVL1 and DVL2 may be involved during early stages of the disease, while DVL3 may have a role in later phases and together with TCF1 and LEF1 promotes the activation of Wnt signalling.